An ex vivo RT-qPCR-based assay for human peripheral leukocyte responsiveness to glucocorticoids in surgically induced inflammation - Gråberg T; Strömmer L; Hedman E; Uzunel M; Ehrenborg E; Wikström AC (Dove Medical Press, 2015)
Truls Gråberg,1 Lovisa Strömmer,1 Erik Hedman,2 Mehmet Uzunel,3 Ewa Ehrenborg,4 Ann-Charlotte Wikström5 1Division of Surgery, Department of Clinical Science, Intervention and Technology (CLINTEC), Karolinska Institutet, 2Department of Clinical Pharmacology, Karolinska University Hospital, 3Division of Therapeutic Immunology, Department of Laboratory Medicine, 4Atherosclerosis Research Unit, Department of Medicine, Solna, 5Unit of Translational Immunology, Department of Medicine, Solna, Karolinska Institutet, Stockholm, Sweden Introduction: An assay to determine glucocorticoid (GC) responsiveness in humans could be used to monitor GC non-responsiveness in states of GC insufficiency and could provide a tool to adapt GC treatment to individual patients. We propose an ex vivo assay to test GC responsiveness in peripheral leukocytes. The assay was evaluated in a human experimental model of surgery-induced inflammation. Patients and methods: Changes in expression of the GC-regulated genes GILZ, IL1R2, FKBP5, and HLA-DR and glucocorticoid receptor alpha (GRα) were determined by reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) in peripheral leukocytes from surgical patients and healthy blood donors (total n=60) in response to low (1 nM) and high (1 µM) dexamethasone (DEX). The final selection of a suitable endogenous control gene was based on the studies of stability during DEX treatment and inflammation. Correlations between pre- and postoperative GC-induced gene expression, the postoperative systemic inflammatory and metabolic response (CRP, IL-6, white blood cell count, cytokines, resistin, free fatty acids, glucose, insulin, and adiponectin), and the clinical outcome were analyzed. The length of stay in the intensive care unit (ICU-LOS), the length of stay in the hospital, and postoperative complications were used to measure clinical outcome. Results: When the blood donors were compared to the patients, there were no significant differences in the regulation of the genes in response to DEX, except for GRα. Preoperative, but not postoperative, gene regulation of GILZ and GRα was negatively correlated to ICU-LOS (P<0.05 and P<0.01, respectively). Preoperative GILZ and FKBP5 gene regulation was negatively correlated to postoperative systemic TNFα and MIP-1α levels. Conclusion: We suggest that this assay could be used to determine GC responsiveness. An alteration in preoperative GC responsiveness may be related to a patient's ability to recover from surgically induced inflammatory stress. Keywords: glucocorticoid responsiveness, gene regulation, clinical outcome, GILZ, GRα, cytokines